The management of vesicoureteral reflux in children - Nurul Akbar; Arry Rodjani (Indonesian Pediatric Society, 2010)
Vesicoureteral reflux (VUR) is defined as retrograde flow of urine from the bladder to the ureter. Â It is usually asymptomatic but commonly found in children with urinary tract infection (UTI). The prevalence is about 1-2% in general pediatric population.1 However, the prevalence in children with UTI is much higher, reaching 30-57%.1,2 Similar prevalence (45.8%) is also reported in CiptoMangunkusumo Hospital. 3